Overview of English Language Ability for Information Technology Student:: Analysis for ESP (English For Specific Purpose) Need - Munfadlila, Asef Wildan (Indonesian Research Journal on Education, 2024)
Needs analysis can be a valuable tool for English for Specific Purposes (ESP) lecturers to identify the primary requirements or needs of their students and to identify the areas in which their skills are deficient. The data for this study were gathered from a variety of sources, such as classroom observation protocols, questionnaires, and semi-structured interviews with English lecturers at Bina Sehat University PPNI Mojokerto. The data analysis results provide significant insights into the instruction of English for Information Technology courses. The investigation demonstrated that English for Information Technology courses prioritize receptive skills (i.e., reading and listening). Additionally, it has been reported that speaking, reading, and writing abilities are more essential than others. The data analysis is instrumental in identifying the most critical language duties within the context of informatics studies. Lastly, lecturers of English for Information Technology are requested to provide pertinent recommendations in order to enhance the content of the English for Information Technology curriculum that is taught to informatics students. The study concludes with implications for course designers and recommendations for future research, as a result of these findings.